MARKETING INFORMATION SYSTEMS IN THE HEALTH SECTOR: A PRACTICE IN HOSPITALS IN TURKEY AND JORDAN (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Health tourism, showing development in the last twenty years in the world, has emerged as an alternative tourism. Health tourism, very quickly developing among alternative tourism options, is an important profit tool since it is increasing the number of business enterprises serving in this field. In this sense, marketing objectives set out in the health services is very diverse. The main objective of the health service is to determine accurately the demands of the target customer and meeting their needs and demands at the highest level to satisfy patients/customers. In this research perception on marketing information systems of public and private hospital managers in Turkey (Gaziantep) and Jordan (Amman) was investigated and perception of patients sought medical treatment in the hospitals of these countries examined using the survey technique. It is confirmed that patients in these countries have different perceptions in terms of hospitals, general services, health services and customer satisfaction. According to the resulting data, there is no difference in perception of managers in these countries on marketing information systems.